2019
DOI: 10.26717/bjstr.2019.12.002301
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer: The Accuracy of The Paus in Detecting pN2 and Factors that Lead to the True- and False-Negative Results

Abstract: About 70% of early breast cancer cases axillary lymph nodes are intact and surgical axillary intervention is unnecessary. There is an ongoing search for non-invasive methods to evaluate the status of axillary lymph nodes in order to prevent Axillary Lymph Node Dissection (ALND) or Sentinel Lymph Node Biopsy (SLNB). Patients with normal axillary physical exam and ultrasound rarely harbor a large nodal disease burden (pN2). There are studies suggesting that the Preoperative Axillary Ultrasound (PAUS) can replace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 18 publications
2
5
1
Order By: Relevance
“…Some previous studies have reported associations between higher tumor grade (G3) and an increased likelihood of false-negative PAUS results [2,11]. However, we did not find any difference in the false-negative rate depending on tumor grade.…”
Section: Discussioncontrasting
confidence: 90%
See 4 more Smart Citations
“…Some previous studies have reported associations between higher tumor grade (G3) and an increased likelihood of false-negative PAUS results [2,11]. However, we did not find any difference in the false-negative rate depending on tumor grade.…”
Section: Discussioncontrasting
confidence: 90%
“…The false-negative rate in the pT2-pT4 group was 8.2%, and in the pT1 group, it was 1.7%, being very similar to the rate in our study [10]. Several studies have demonstrated that larger tumor sizes were more often associated with false-negative results of ultrasound [2,11,[41][42][43]. These results show that smaller tumors are generally associated with a lower likelihood of nodal positivity, so a lower false-negative rate could be expected with lower pathologic T size.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations